IMPLEMENTASI METODE REPATITIVE PRACTICE PADA SYAIR MADURA DALAM MENINGKATKAN PEMAHAMAN BELAJAR SISWA MADRASAH IBTIDAIYAH - Mushfi El Iq Bali, Muhammad; Nur Avia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the application of the Repetitive Practice method in improving students' understanding of the Siroh Nabawiyah material. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and document analysis, and supported by the results of the pretest and posttest. The research procedure included direct observation of the learning process, interviews with teachers and students, and data analysis using a thematic approach. The results showed that this method was effective in improving students' understanding, with an average score increase of 20%-30% in the posttest results compared to the pretest. Student activities during learning, such as humming poetry in groups, reflected enthusiasm and active involvement. Teachers stated that this method helped create a fun and collaborative learning atmosphere, while students admitted that they found it easier to understand and memorize the material through creative repetition. This study offers novelty by combining elements of art and repetition in learning, which can significantly improve students' memory. However, this study has limitations in covering subjects that only involve one class in one school. For further research, it is recommended to expand the application of this method to a wider range of materials and learning contexts. The results of this study provide an important contribution to the strategy for developing creativity-based learning.